2021
DOI: 10.1093/plankt/fbab024
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal genetic structure in theDaphnia pulexcomplex from Sierra Nevada lakes (Spain): reproductive mode and first record of North AmericanD.cf.pulexin European alpine lakes

Abstract: Daphnia is a good model organism for studying factors affecting dispersal and patterns of genetic diversity. Within this genus, the Daphnia pulex species complex includes lineages from North America and Europe, with some considered invaders in various continents, although their colonization history is poorly known. We used mitochondrial DNA and microsatellite markers to identify the D. pulex complex lineages in Sierra Nevada, determine their reproductive mode and reconstruct their genetic history (over the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 98 publications
5
10
0
Order By: Relevance
“…However, Dane et al (2020) noted that the limitations of their study were in the small sample sizes (tens of diapausing eggs analysed in each research site) and limited resolution of the genetic markers used (eight microsatellite loci), which might have caused a failure to detect minor genotypes coexisting with the major one. This is also the case for Conde‐Porcuna et al (2021).…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…However, Dane et al (2020) noted that the limitations of their study were in the small sample sizes (tens of diapausing eggs analysed in each research site) and limited resolution of the genetic markers used (eight microsatellite loci), which might have caused a failure to detect minor genotypes coexisting with the major one. This is also the case for Conde‐Porcuna et al (2021).…”
Section: Introductionsupporting
confidence: 71%
“…We can extract DNA from these preserved diapausing eggs, and thereby reconstruct population genetic dynamics (Burge et al, 2018; Orsini et al, 2016). Although previous studies have revealed the evolutionary processes of Daphnia using diapausing eggs (e.g., Decaestecker et al, 2007; Hairston et al, 1999; Stoks et al, 2016), only three prior studies have observed long‐term genetic dynamics of Daphnia species including the early stage of colonisation (Conde‐Porcuna et al, 2021; Dane et al, 2020; Möst et al, 2015). Möst et al (2015) analysed 40 years of long‐term genetic dynamics of colonisation and establishment by Daphnia pulicaria that consisted of cyclic parthenogenetic lineages and possibly a few obligate parthenogenetic lineages.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations